Reconsideration of Guidance for Patients with Eating and Swallowing Disorders: Training for Adult Patients with Dysphagia - OKAMOTO, Isao (THE JAPANESE JOURNAL OF COMMUNICATION DISORDERS, 2000)
This paper reports in detail on practical training for a patient with severe dysphagia. Though the patient was seriously handicapped, I found that our training was able to bring about continued improvement. Among the factors responsible for this, I discuss how the medical staff patiently continued the medical treatment and training and, by enabling the patient to eat through her own efforts, were able to draw out her desire to live. While reconsidering the importance of “eating” for people to live humanely, I state my personal opinion about the role of the speech therapist and concrete methods to help a patient with dysphagia. I also presented two suggestions concerning the “team approach” for rehabilitating a patient with dysphagia and the “professional ethics” of the speech therapist.